Extranodal marginal zone lymphoma clonotypes are detectable prior to eMZL diagnosis in tissue biopsies and peripheral blood of Sjögren’s syndrome patients through immunogenetics - Kolijn, P. Martijn; Huijser, Erika; Wahadat, M. Javad; van Helden-Meeuwsen, Cornelia G.; van Daele, Paul L. A.; Brkic, Zana; Rijntjes, Jos; Hebeda, Konnie M.; Groenen, Patricia J. T. A.; Versnel, Marjan A.; Thurlings, Rogier M.; Langerak, Anton W. (Frontiers in Oncology, 2023)
Introduction Activated B cells play a key role in the pathogenesis of primary Sjögren’s syndrome (pSS) through the production of autoantibodies and the development of ectopic germinal centers in the salivary glands and other affected sites. Around 5-10% of pSS patients develop B-cell lymphoma, usually extranodal marginal zone lymphomas (eMZL) of the mucosa-associated lymphoid tissue (MALT). The aim of the current study is to investigate if the eMZL clonotype is detectable in prediagnostic blood and tissue biopsies of pSS patients. Methods/Results We studied prediagnostic tissue biopsies of three pSS patients diagnosed with eMZL and four pSS controls through immunoglobulin (IG) gene repertoire sequencing. In all three cases, we observed the eMZL clonotype in prediagnostic tissue biopsies. Among controls, we observed transient elevation of clonotypes in two pSS patients. To evaluate if eMZL clonotypes may also be detected in the circulation, we sequenced a peripheral blood mononuclear cell (PBMC) sample drawn at eMZL diagnosis and two years prior to eMZL relapse in two pSS patients. The eMZL clonotype was detected in the peripheral blood prior to diagnosis in both cases. Next, we selected three pSS patients who developed eMZL lymphoma and five additional pSS patients who remained lymphoma-free. We sequenced the IG heavy chain (IGH) gene repertoire in PBMC samples taken a median of three years before eMZL diagnosis. In two out of three eMZL patients, the dominant clonotype in the prediagnostic PBMC samples matched the eMZL clonotype in the diagnostic biopsy. The eMZL clonotypes observed consisted of stereotypic IGHV gene combinations (IGHV1-69/IGHJ4 and IGHV4-59/IGHJ5) associated with rheumatoid factor activity, a previously reported feature of eMZL in pSS. Discussion In conclusion, our results indicate that eMZL clonotypes in pSS patients are detectable prior to overt eMZL diagnosis in both tissue biopsies and peripheral blood through immunogenetic sequencing, paving the way for the development of improved methods of early detection of eMZL.